Mechanisms of reactive gliosis in cortical and spinal cord astrocytes at different developmental stages - Hareeri, Rawan (2020)
Astrocytes represent a major class of glial cells responsible for maintaining the microenvironment of the central nervous system. They are thought to play an important role in the development of many diseases, such as stroke, neurodegenerative disease and pain. It is apparent that astrocytes become reactive during the onset of these diseases to form foci of reactive gliosis; however, the mechanisms of reactive gliosis are poorly characterised. This thesis therefore aims to investigate the mechanisms underlying reactive gliosis astrocytes in different CNS regions and during development in vitro.